Montgomery on informed consent: an inexpert decision?. Issue 2 (25th January 2016) - Montgomery, Jonathan; Montgomery, Elsa
Abstract : Montgomery v Lanarkshire HB is a deeply troubling decision when read closely. Paradoxically, its ruling supporting the principle of autonomy could be justified only by disregarding the individual patient's actual choices and characteristics in favour of a stereotype. The decision demonstrates a lack of expertise in dealing with specific clinical issues and misrepresents professional guidance. More fundamentally, it fails to appreciate the nature of professional expertise. This calls into question the competence of the courts to adjudicate on matters of clinical judgement and makes an attractive formulation of the test for disclosure obligations inherently unpredictable.